Boron nitride nanosheets functionalized channel scaffold favors microenvironment rebalance cocktail therapy for piezocatalytic neuronal repair. (May 2021) - Qian, Yun; Xu, Yang; Yan, Zhiwen; Jin, Yi; Chen, Xuan; Yuan, Wei-En; Fan, Cunyi
Abstract: Persistent electrical stimulation by a mechanically actuated channel scaffold with porous and layered architecture is a promising strategy to facilitate neuronal microenvironment rebalance and locomotor recovery. Nevertheless, the relevant studies to date only reported preliminary findings but did not comprehensively evaluate its in-depth biological effects and mechanisms. To translate this smart scaffold into clinical application, biocompatibility and efficacy of the piezocatalytic nanoscaffold should be verified in vitro and in vivo. A novel 'microenvironment rebalance cocktail therapy' is proposed in this study. The piezoelectric boron nitride nanosheets (BNNS) functionalized polycaprolactone (PCL) channel scaffold displays high elasticity, hydrophilicity and biocompatibility, and stimulates cellular excretion of neurotrophic factors by increasing bioelectrical signal transduction under ultrasonic actuation in vitro. In addition, the scaffold modulates reactive oxygen species level and restores energy metabolic balance to maintain Schwann cell viability. The smart BNNS@PCL porous scaffold induces microvessel regrowth into neurons and reverses muscular atrophy after denervation in a severe sciatic nerve defect model in vivo. The design concept will be applicable in manufacture of an artificial bioelectrical system for advanced piezocatalytic nerve therapies. Graphical Abstract: A piezoelectric scaffold is fabricated by 3D layer-by-layer droplet spraying method and favors microenvironment rebalance cocktail therapy that includes: (1) mechano-informed scaffold converts mechanical stimuli into electricity to restore bioelectrical signaling. (2) the scaffold attenuates the immune response by reducing ROS level and rectifies the metabolic disturbance. (3) internal regrowth of microvessels improves structural regeneration, muscle reinnervation and locomotor recovery. ga1 Highlights: A piezoelectric scaffold is fabricated by 3D layer-by-layer droplet spraying method. The 3D nanoscaffold favors a novel microenvironment rebalance cocktail therapy. The 3D nanoscaffold improves muscle reinnervation and locomotor recovery.